Light-Trap Catch of the European Corn-borer (Ostrinia nubilalis HAbner) and Setaceous Hebrew Character (Xestia c-nigrum L.) in Connection with the Height of Tropopause (Global Journal of Medical Research, 2014)
In present paper we examined the connection between height of tropopause and the light-trap catch two moth species. The data of European Corn-borer come from the Hungarian national light-trap network between 1959 and 1973, and the Setaceous Hebrew Character come from the forestry light-trap network between 1961-1970. Groups were made for data of the height of tropopause. The relative catch values of the examined species were categorised according to the characteristics of tropopause on each day, after it these values were summarised, averaged and depicted. We defined the parameters of the regression equations. We have found a close positive correlation between the height of the tropopause and relative catch of Setaceous Hebrew Character, but only the lowest and highest values of the tropopause reduce or rather increase of the light trap catch of the European Corn-borer.
Keywords: light trapping; tropopause; ostrinia nubilalis; xestia c-nigrum